A Traffic Congestion Pricing Model for Eminonu District - Yuksel, Haluk; Yardim, Mustafa Sinan; Gursoy, Mustafa (TURKISH CHAMBER CIVIL ENGINEERS, 2010)
An investigation on applicability of a congestion pricing scheme to the Eminonu District, which is subject to heavy traffic problems in the Historical Peninsula of Istanbul, has been conducted. The area borders are set; field studies are performed to determine speed-flow characteristics of the roads and the demand function for automobile users. Akcelik and MTC speed-flow models are found suitable to represent the area's traffic. A computer program is developed to assess the optimum toll under many different conditions with higher sensitivity. As a result, optimum congestion toll rates for different scenarios are calculated and it is concluded that the congestion pricing application would have a decreasing effect on the automobile road traffic of 15-40% and increase the mean traffic speed approximately 15-25 km/h.
Keywords: Congestion pricing; speed-flow relationship; Eminonu; logit modal split model; TRAVEL-TIME; HONG-KONG; SINGAPORE; Engineering